Minimizing Labor Disputes: Processing Grievances, Conciliation and Mediation - William F. White (Washington University Law Quarterly, 1949)
I have jotted down a few habits that I am afraid labor and management negotiators sometimes are found guilty of which do not make for good relationships in negotiations, nor result in a good practical contract.
Keywords: Collective bargaining; Labor law